The Ecology of Cyanobacteria Their Diversity in Time and Space - Whitton, Brian A.; Potts, Malcolm. (Springer Netherlands, 2002)
Cyanobacteria make a major contribution to world photosynthesis and nitrogen fixation, but are also notorious for causing nuisances such as dense and often toxic `blooms' in lakes and the ocean. The Ecology of Cyanobacteria: Their Diversity in Time and Space is the first book to focus solely on ecological aspects of these organisms. Its twenty-two chapters are written by some thirty authors, who are leading experts in their particular subject. The book begins with an overview of the cyanobacteria - or blue-green algae, for those who are not specialists - then looks at their diversity in the geological record and goes on to describe their ecology in present environments where they play important roles. Why is one of the key groups of organisms in the Precambrian still one of the most important groups of phototrophs today? The importance of ecological information for rational management and exploitation of these organisms for commercial and other practical purposes is also assessed. Accounts are provided of nuisances as well as the ecology of the commercially successful Spirulina and the role of cyanobacteria in ecosystem recovery from oil pollution. Many chapters include aspects of physiology, biochemistry, geochemistry and molecular biology where these help general understanding of the subject. In addition there are three chapters dealing specifically with molecular ecology. Thirty-two pages of colour photos incorporate about seventy views and light micrographs. These features make the book valuable to a wide readership, including biologists, microbiologists, geologists, water managers and environmental consultants. The book complements the highly successful The Molecular Biology of Cyanobacteria already published by Kluwer.